Mitochondrial DNA analyses and ecological niche modeling reveal post‐LGM expansion of the Assam macaque (Macaca assamensis) in the foothills of Nepal Himalaya. Issue 3 (14th March 2018) - Khanal, Laxman; Chalise, Mukesh K.; He, Kai; Acharya, Bipin K.; Kawamoto, Yoshi; Jiang, Xuelong
Abstract : Genetic diversity of a species is influenced by multiple factors, including the Quaternary glacial‐interglacial cycles and geophysical barriers. Such factors are not yet well documented for fauna from the southern border of the Himalayan region. This study used mitochondrial DNA (mtDNA) sequences and ecological niche modeling (ENM) to explore how the late Pleistocene climatic fluctuations and complex geography of the Himalayan region have shaped genetic diversity, population genetic structure, and demographic history of the Nepalese population of Assam macaques ( Macaca assamensis ) in the Himalayan foothills. A total of 277 fecal samples were collected from 39 wild troops over almost the entire distribution of the species in Nepal. The mtDNA fragment encompassing the complete control region (1121 bp) was recovered from 208 samples, thus defining 54 haplotypes. Results showed low nucleotide diversity (0.0075 ± SD 0.0001) but high haplotype diversity (0.965 ± SD 0.004). The mtDNA sequences revealed a shallow population genetic structure with a moderate but statistically significant effect of isolation by distance. Demographic history analyses using mtDNA sequences suggested a post‐pleistocene population expansion. Paleodistribution reconstruction projected that the potential habitat of the Assam macaque was confined to the lower elevations of central Nepal during the Last Glacial Maximum. With the onset of the Holocene climatic optimum, the glacial refugia population experienced eastward range expansion to higher elevations. We conclude that the low genetic diversity and shallow population genetic structure of the Assam macaque population in the Nepal Himalaya region are the consequence of recent demographic and spatial expansion. Abstract : Fine scale sampling and molecular analysis reveals that "Nepal population" of Assam macaque ( Macaca assamensis ) has low genetic diversity and shallow population genetic structure lacking signature of strong riverine barrier effects. Molecular data and ecological niche modeling complimentarily support the post‐Pleistocene demographic and spatial expansion of the species in Nepal Himalaya. The species requires its taxonomic revision using multi‐locus molecular approaches comparing with the recently described species like M. leucogenys, M. munzala, and conspecific populations from Bhutan and north‐eastern India.